Design and development of a grant management system - Tan, Melvin Wei Jian (2017)
Research grants are made available by various organization to help fund research efforts made by individuals, universities and other groups. A research grant can cover different subject matters such as general research where anyone can simply participate or specific research like the field of medicine where participants are required a set of skills and knowledge. In Nanyang Technological University (NTU), research grants are emailed to school faculty members which can cause inconvenience to the recipient as not all recipients will be interested in the research grant. Hence, a web-based system that can handle the process of managing and distributing of grants is suggested to reduce such inconvenience. The purpose of this project is to design and develop a web-based grant distribution system with the intention of helping the users to gather researchers who are interested in participating and meanwhile minimizing the receiving of irrelevant grants. This system will be the main platform used by the research centers or schools in the university to manage and distribute the grant information. By the end of this project, the system is a stable and complete system which fulfills the requirement of the project. However, for future enhancement, the system can be implemented on a mobile platform to achieve better usage.